6 - Book Reviews: « Principles and Practice of Public Administration in Nigeria,» by Augustus ADEBAYO; published by John WILLE Y and Sons Ltd in association with Spectrum Books Ltd., Ibadan, 1981 ; 193 pages; paperback; price: N 4.00. - HEINECKE, H. (Africa Development, 1981)
P. HEINECKE, Faculty of Administration, Ahmadou Bello University, Zaria, Nigeria.